(untitled) (University Journal of Zoology, Rajshahi University, 2012)
The genotypic variability and heritability for nine quantitative characters in 65 varieties of silkworm, B. mori L. have been investigated. Variation among genotypes were highly significant (p<0.001) for all the characters indicating the existence of a real difference among the genotypes which are suitable for breeding purposes. The highest heritability was obtained for shell weight followed by filament size (FS), filament length (FL), expected cocoon yield out of 100 dfls (ECY), surviving percentage of larvae (SPL), cocoon weight (CW), egg hatching percentage (EHP) and mature larval weight (MLW). Comparatively high heritability accompanied by a genetic advance was recorded for FL and total number of eggs laid per female (TEL) indicating the importance of additive gene effects of these characters, but shell weight, cocoon weight and filament size showed high heritability and low genetic advance indicating the involvement of non-additive gene systems in the inheritance of these characters. So selection on the basis of these characters, with relatively more emphasis upon filament length and total number of eggs laid per female to obtain high yielding varieties of B. mori is suggested. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10744 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp.33-36